2019
DOI: 10.17113/ftb.57.04.19.6250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biofermentation with Taxifolin on Physicochemical and Microbiological Properties of Cold-Smoked Pork Sausages

Abstract: The aim of this work is to evaluate the effect of taxifolin on the physicochemical and microbiological properties of cold-smoked pork sausages produced using different commercial starter cultures with Leuconostoc carnosum and with a mixture of Pediococcus pentosaceus and Staphylococcus xylosus. Ultra performance liquid chromatography analysis demonstrated that after 181 days of storage total taxifolin content was the highest in samples with taxifolin and L. carnosum (60 %), compared to the first day of storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…As a natural product, TAX has multiple biological functions. In recent years, it has been used in many fields, such as antioxidation to scavenge free radicals (Li et al, 2017;Gustiene et al, 2019;Lektemur Alpan et al, 2020), anti-obesity (Su et al, 2022), anti-inflammation (Wu et al, 2019), and other areas. In the current research, we found that adding TAX to the basal diet could improve boar semen quality by increasing sperm motility and sperm concentration.…”
Section: Discussionmentioning
confidence: 99%
“…As a natural product, TAX has multiple biological functions. In recent years, it has been used in many fields, such as antioxidation to scavenge free radicals (Li et al, 2017;Gustiene et al, 2019;Lektemur Alpan et al, 2020), anti-obesity (Su et al, 2022), anti-inflammation (Wu et al, 2019), and other areas. In the current research, we found that adding TAX to the basal diet could improve boar semen quality by increasing sperm motility and sperm concentration.…”
Section: Discussionmentioning
confidence: 99%